Economic Activities of Mining Production and Agricultural Economic Growth in South Africa - Ncanywa, Thobeka (Journal of Reviews on Global Economics, 2019)
South Africa is experiencing declining mining sector output that is economically detrimental as it leaves large numbers of mining workers unemployed. Unskilled retrenched mine workers from about 5,906 abandoned mines resulted in a discrete jump in the productive wealth of poor South Africans, as trends in mining profits declined. It is precisely this challenge that made economic succession planning in South African mines a potentially attractive policy option in the fight against poverty. This paper provides some of the first well-identified estimates of the viability of how post mining transformation can take place through agricultural production. Therefore, the paper aims to examine the relationship between the mining production economic activities and the agricultural economic growth using South African data. Employing the autoregressive distributive lag approach and impulse response functions, it has been found that the mining production has a significant long run relationship and can positively influence the agricultural economy. This is in line with the views of Rostow (1959) that mining production can be associated with agricultural activities and be used as a tool for post mining transformation. Therefore, it can be recommended that mines can engage to formulate policies that address post mining transformation into agricultural activities to redirect labor skills when the time of closing mines come. Suggested policies range from skill redirection of mine workers to agricultural activities. For instance, plantation of some fibrous plants that can grow well in mining land, and engage in some more economic activities like manufacturing and tourism of those agricultural products.